FEMINISME ISLAM: Perspektif Islam Kontemporer - Muqoyyidin, Andik Wahyun (Kopertais Wilayah X Jawa Tengah, 2013)
AbstractGender is one of a number of contemporary discourse that can be called that is enough to get the attention of many people, from the teenagers, among movement activists, academics and students, the legislature and government, to the clergy. The purpose of this discourse is a close social injustice based on gender differences, the next attempt to bring about equality between men and women on the social aspects. Gender discourse can be categorized into at least four appearances, namely as a movement, a philosophical discourse, the development of social issues to religious issues, and as an approach in the study of religion. This paper will discuss the perspectives of gender equality as conceived by Muslim feminists. Generally it can be stated that the goal of feminism is the struggle to achieve equality, dignity, and freedom of women in selecting and managing the life and body, both inside and outside the household.Kata Kunci: kesetaraan, gender, gerakan, feminisme Islam